Pastoralism, biodiversity and health: Why pastoralists must be central to nature conservation - Scoones, Ian (2022)
This five-minute video by Ian Scoones, of the Institute of Development Studies, in the UK, argues that ensuring good human health and preventing zoonotic disease outbreaks requires healthy ecosystems. For rangelands around the world, pastoralists are essential, and central, to nature conservation. Rangelands, where pastoralists live, make up more than half of the world’s land surface and are vitally important. These are highly biodiverse ‘open ecosystems’, where trees and grasses are mixed in variegated patches maintained by the grazing of wild and domesticated animals.